Are Dental Implants the Answer to Tooth Loss in Patients with Parkinson's Disease?. Issue 2 (June 2015) - Packer, Mark E
Individuals with Parkinson's disease present a challenge to dental clinicians as this degenerative disease leads to problems accessing care and maintaining an adequate level of oral health. This article provides an overview of the implications of Parkinson's disease on oral health and explores the role of dental implants in the management of such patients.